2001
DOI: 10.1094/cchem.2001.78.6.654
|View full text |Cite
|
Sign up to set email alerts
|

Bread Quality Relationship with Rheological Measurements of Wheat Flour Dough

Abstract: The rheological properties of wheat doughs prepared from different flour types, water contents, and mixing times for a total of 20 dough systems were studied. The results were compared with the results of standard baking tests with the same factors. Water and flour type had a significant effect on storage modulus (G′) or phase angle measured by an oscillatory test both in the linear viscoelastic region and as a function of stress, and on compressional force measured as a function of time. The correlation of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 13 publications
5
31
0
2
Order By: Relevance
“…2b and c). This phenomenon is attributed simply to the dilution of constituents, and it has been well documented for wheat flour doughs (Autio et al, 2001) and for gluten-free doughs (Lazaridou et al, 2007;Ronda et al, 2013). It was also observed that psyllium and HPMC increased the elastic modulus (G 0 ) (Fig.…”
Section: Dough Rheologymentioning
confidence: 84%
“…2b and c). This phenomenon is attributed simply to the dilution of constituents, and it has been well documented for wheat flour doughs (Autio et al, 2001) and for gluten-free doughs (Lazaridou et al, 2007;Ronda et al, 2013). It was also observed that psyllium and HPMC increased the elastic modulus (G 0 ) (Fig.…”
Section: Dough Rheologymentioning
confidence: 84%
“…Several rheological techniques, including oscillation, stress relaxation, creep and creep -recovery measurements have been used in many studies to probe the fundamental mechanical properties of gluten (Janssen et al, 1996a;Lee and Mulvaney, 2003) and wheat doughs (Weipert, 1990;Janssen et al, 1996b;Baltsavias et al, 1997;Phan-Thien and Safari-Ardi, 1998;Safari-Ardi and Phan-Thien, 1998;Edwards et al, 1999;Edwards et al, 2001;Edwards et al, 2003;Lazaridou et al, 2007) as well as to establish the relations between the properties and quality attributes of the end -product (Autio et al, 2001;Carson and Sun, 2001;Wang and Sun, 2002;Dobraszczyk and Morgenstern, 2003;Lazaridou et al, 2007).…”
mentioning
confidence: 99%
“…Different empirical methods based on classical Extensograph, Alveograph, Farinograph, and Mixograph instruments are currently employed to obtain accurate data on the baking properties of the respective flour, by simulating the bread making steps (Autio et al 2001;Chung et al 2001;Chiotelli et al 2004;Collar et al 2007).…”
mentioning
confidence: 99%